Estudio de correlación entre tres pruebas de rastreo cognitivo en población sin deterioro cognitivo (2012)
Cognitive screening tests allow assessing a patient’s comprehensive mental status briefly. Mini-Mental State Examination test —MMSE— is the most used instrument; however, this test has some inconveniences for clinical usage since it does not provide adequate accuracy and specificity when detecting cognitive impairment, hence, causing misdiagnosis. On the other hand, Rapid Assessment of Cognitive Functions (RACF) test —NEUROPSI especially—, offers broader measurement options than the Mini-Mental, thus, overcoming the aforementioned flaws. The aim of this study was to determine any possible correlation among these screening tests. The tests were applied to 118 subjects without cognitive impairment. Positive correlations were found between NEUROPSI and MMSE, RACF and MMSE, and NEUROPSI and RACF. The presence of positive correlations among the three screening tests suggests the option of implementing NEUROPSI and RACF as alternatives to MMSE in the assessment of cognitive impaired patients.